Food consumption patterns of first-year students at higher educational institution’s residences - Macozoma, Sibusiso (Cape Peninsula University of Technology, 2023)
Dietary habits play an important role in people’s health and mortality, thereby placing nutrition as an agent for a healthy balanced life for a prolonged life as such nutritional foods are the basis for lifelong survival against communicable diseases. Hence, variants in nutrition (such as fruits, vegetables, nuts, dairy products, & staple foods) are a vehicle for the well-being of the human body and mind. Hence, this study aimed to investigate food consumption patterns of first-year students living at residence facilities of higher education institutions in the Cape Town Metropole. The study further aimed at identifying the factors that cause a change in consumption patterns of first-year students living at residence facilities of higher education in the Cape Town Metropole: what the respondents now ate in relation to what they ate while still at home. Furthermore, this research aimed at recommending a balanced diet for healthy living at residence facilities of higher education based on the findings. In meeting the set objectives for this research, a quantitative research method was applied in a form of a structured survey questionnaire (close-ended). The survey questionnaire was divided into three sections (Section A, B & C); the first section focused on the demographic information, the second section investigated the availability, access, and frequency of food consumption; and the third section provided food diversity lists that illustrate different foods that are likely to be consumed by first-year students at residential facilities. The research instrument used a categorical manner questionnaire format for easy processing of the data. The study collected 150 questionnaires from first-year higher education students at the two residences in the Cape Town Metropole area. The received data were acquired using snowballing and convenient sampling procedures. The obtained data were analysed using Stata Statistical Software version 15. The first stage of data analysis employed univariate descriptive analyses (frequencies, mean and standard deviation) to describe respondents’ profiles and views; and the second stage used Logistic Regression analysis for inferential statistics. The final stage of data analysis conducted reliability tests on the categorical variables in Section B and Section C parts of the questionnaire using Cronhan’s Q-Test. Findings from this study reveal that first-year students at institutions of higher learning food consumption patterns in the Cape Town Metropole have changed (68%) since they became responsible for their own catering. Convenience and affordability were found to be the main drivers of change in food consumption patterns of students at residential facilities in the Cape Town Metropole area. Those with funding receive variants of food items when compared to their counterparts without funding. Also, those with higher incomes are most likely not affected by a dietary change in their eating habits. Therefore, the study suggests that institutions of higher learning create farming spaces for university students that will be inclusive to all students irrespective of discipline. This will allow students to earn an income through farming in universities, which will create a culture where farming becomes part of South African society and is perceived as a means of expanding income as well as being of nutritional benefit to South African society at large. The use of land for farming in universities will create a culture where farming becomes fashionable to youngsters, thereby curbing food insecurity in the country. Further research may look at the dietary consumption of students in institutions of higher learning across disciplines and levels to identify similarities or differences among these groups as this study was limited to first-year students only.
Thesis (MTech (Tourism and Hospitality Management))--Cape Peninsula University of Technology, 2023
Keywords: Food habits; College freshmen -- Nutrition; Academic achievement -- Nutritional aspects; College freshmen -- Health and hygiene; Health promotion